Photocatalytic degradation of microcystin-LR and off-odor compounds in water under UV-A and solar light with a nanostructured photocatalyst based on reduced graphene oxide-TiO2 composite. Identification of intermediate products. - Fotiou, T.; Triantis, T.M.; Kaloudis, T.; Pastrana-Martínez, L.M.; V. Likodimos; P. Falaras; Silva, A.M.T.; Hiskia, A. (Industrial and Engineering Chemistry Research, 2013)
Microcystin-LR (MC-LR) is the most common and toxic variant of the group of microcystins (MCs) produced during the formation of harmful cyanobacterial blooms. Geosmin (GSM) and 2-methylisoborneol (MIB) may also be produced during cyanobacterial blooms and can taint water causing undesirable taste and odor. The photocatalytic degradation of MC-LR, GSM, and MIB in water under both UV-A and solar light in the presence of reduced graphene oxide-TiO2 composite (GO-TiO2) was studied. Two commercially available TiO 2 materials (Degussa P25 and Kronos) and a reference TiO2 material prepared in the laboratory (ref-TiO2) were used for comparison. Under UV-A irradiation, Degussa P25 was the most efficient photocatalyst for the degradation of all target analytes followed by GO-TiO 2, ref-TiO2, and Kronos. Under solar light irradiation GO-TiO2 presented similar photocatalytic activity to Degussa P25, followed by Kronos and ref-TiO2 which were less efficient. Intermediate products formed during the photocatalytic process with GO-TiO 2 under solar light were identified and were found to be almost identical to those observed by Degussa P25/UV-A. Assessment of the residual toxicity of MC-LR during the course of treatment with GO-TiO2 showed that toxicity is proportional only to the remaining MC-LR concentration. The photocatalytic performance of GO-TiO2 was also evaluated under solar light illumination in real surface water samples, and GO-TiO2 proved to be effective in the degradation of all target compounds. © 2013 American Chemical Society.
cited By 49